The use of porous polyethylene (Medpor) lower eyelid spacers in lid heightening and stabilisation. Issue 9 (17th August 2004) - Tan, J; Olver, J; Wright, M; Maini, R; Neoh, C; Dickinson, A J
Abstract : Background/aims: The management of lower eyelid retraction can be challenging, and established techniques to correct it are not always successful. Previous reports have suggested a role for the ultrathin high density porous polyethylene lower eyelid spacer (Medpor LES) in such patients. The authors report the experience of three surgeons implanting Medpor LES over 1 year, and ascertain whether such implants are a safe and effective alternative to autogenous spacers. Methods: A prospective, interventional, non-comparative case series of consecutive patients. Surgical indications for Medpor LES were noted. Preoperative and postoperative lower marginal reflex distance (L-MRD), vertical palpebral aperture (PA), lagophthalmos, and scleral show inferior to the limbus (LSS) were recorded, together with major and minor complications. Results: 32 patients (35 eyelids) had a Medpor LES inserted, 22/32 under local anaesthetic, and nine with adjunctive procedures. Mean follow up was 22 months (range 15–28 months). The Medpor LES was effective in reducing the palpebral aperture (p<0.001) and lagophthalmos (p = 0.04) and raising the lower eyelid height by reducing both L-MRD (p  =  0.006) and LSS (p<0.001). However there were major complications in 7/32 patients and minor complications in 8/32, most requiring further surgery. Final outcome was good in 24/35 eyelids and satisfactory in 5/35. Conclusions: Despite a good or satisfactory final outcome in the majority of patients, the value of this technique is limited by complications, and should be reserved for those unsuitable for safer techniques.